Bibliometric Mapping of Maqasid Shariah in Financial and Sustainability Studies - Fauzi, Muchamad Rizky; Hasriadi, L.M; Yanti, Wilda (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
This study examines the intellectual development of Maqasid Shariah in the fields of Islamic finance and sustainability over the last ten years. Employing bibliometric and content analyses of Scopus-indexed publications, the results indicate that Indonesia and Malaysia are the foremost contributors to this domain, highlighting their regional preeminence in the integration of ethical, financial, and sustainable governance frameworks. The keyword mapping shows five main thematic clusters that make up the current research landscape: sustainability, Islamic banking, Maqasid Shariah, governance, and innovation. There is a clear progression over time from early studies that looked at compliance and financial performance to newer topics like ESG integration, value-based banking, and fintech-driven sustainability. The findings indicate that Maqasid Shariah has transitioned from a normative framework to an operational paradigm that reconciles ethical objectives with economic performance and environmental stewardship. This change makes Islamic finance a value-driven model that can help with global sustainability goals. The study concludes by urging future researchers to broaden empirical investigations across various sectors and to create hybrid analytical models that amalgamate Maqasid Shariah with digital innovation and sustainability assessment frameworks.